Visual and rapid identification of Chlamydia trachomatis and Neisseria gonorrhoeae using multiplex loop-mediated isothermal amplification and a gold nanoparticle-based lateral flow biosensor - Chen, Xu; Zhou, Qingxue; Yuan, Wei; Shi, Yuanfang; Dong, Shilei; Luo, Xinhua (Frontiers in Cellular and Infection Microbiology, 2023)
Sexually transmitted chlamydia and gonorrhea infections caused by the bacteria Chlamydia trachomatis and Neisseria gonorrhoeae remain a major public health concern worldwide, particularly in less developed nations. It is crucial to use a point of care (POC) diagnostic method that is quick, specific, sensitive, and user-friendly to treat and control these infections effectively. Here, a novel molecular diagnostic assay, combining multiplex loop-mediated isothermal amplification (mLAMP) with a visual gold nanoparticles-based lateral flow biosensor (AuNPs-LFB) was devised and used for highly specific, sensitive, rapid, visual, and easy identification of C. trachomatis and N. gonorrhoeae. Two unique independent primer pairs were successful designed against the ompA and orf1 genes of C. trachomatis and N. gonorrhoeae, respectively. The optimal mLAMP-AuNPs-LFB reaction conditions were determined to be 67℃ for 35 min. The detection procedure, involving crude genomic DNA extraction ( 5 min), LAMP amplification (35 min), and visual results interpretation (<2 min), can be completed within 45 min. Our assay has a detection limit of 50 copies per test, and we did not observe any cross-reactivity with any other bacteria in our testing. Hence, our mLAMP-AuNPs-LFB assay can potentially be used for POC testing to detect C. trachomatis and N. gonorrhoeae in clinical settings, particularly in underdeveloped regions.